GE11-antigen-loaded hepatitis B virus core antigen virus-like particles efficiently bind to TNBC tumor - Zhang, Long; Tang, Lin; Jiang, Yongsheng; Wang, Chenou; Huang, Lijiang; Ding, Ting; Zhang, Tinghong; Li, Huaqiong; Xie, Longteng (Frontiers in Oncology, 2023)
Purpose This study aimed to explore the possibility of utilizing hepatitis B core protein (HBc) virus-like particles (VLPs) encapsulate doxorubicin (Dox) to reduce the adverse effect caused by its off-target and toxic side effect. Methods Here, a triple-negative breast cancer (TNBC) tumor-targeting GE11-HBc VLP was constructed through genetic engineering. The GE11 peptide, a 12-amino-acid peptide targeting epidermal growth factor receptor (EGFR), was inserted into the surface protein loops of VLPs. The Dox was loaded into HBc VLPs by a thermal-triggered encapsulation strategy. The in vitro release, cytotoxicity, and cellular uptake of TNBC tumor-targeting GE11-HBc VLPs was then evaluated. Results These VLPs possessed excellent stability, DOX loading efficiency, and preferentially released drug payload at high GSH levels. The insertion of GE11 targeting peptide caused improved cellular uptake and enhanced cell viability inhibitory in EGFR high-expressed TNBC cells. Conclusion Together, these results highlight DOX-loaded, EGFR-targeted VLPs as a potentially useful therapeutic choice for EGFR-overexpressing TNBC.